A Mie‐Grüneisen mixture Eulerian model for underwater explosion. Issue 3 (2014) - Zongduo Wu; Zhi Zong; Lei Sun
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to provide an improved Mie‐Grüneisen mixture model to simulate underwater explosion (UNDEX). Design/methodology/approach – By using Mie‐Grüneisen equations of state (EOS) to model explosive charge, liquid water and solid structure, the whole fluid field is considered as a multi‐phases mixture under Mie‐Grüneisen EOS. Then by introducing auxiliary variables in Eulerian model and using mass fraction to establish a diffusion balance, a new improved Mie‐Grüneisen mixture model is presented here. For the new reconstructed mixture model, a second order MUSCL scheme with TVD limiter is employed to solve the multi‐phase Riemann problem. Findings – Numerical examples show that the results obtained by Mie‐Grüneisen mixture model are quite closed to theoretical and empirical data. The model can be also used in 2‐D fluid‐structure problem of UNDEX effectively and it is proved that the deformation of structure can be clearly described by mass fraction. Research limitations/implications – The FVM model based on mass fraction can only describe the motion of compressible material under impact. Material failure or large deformation needs a modification about the EOS or implementations of other models (i.e. FEM model). Originality/value – An improved non‐oscillation Mie‐Grüneisen mixture model, which based on mass fraction, is given in the present paper. The present Mie‐Grüneisen mixture model provides a simplified and efficient way to simulate UNDEX. The feasibility of this model to simulate the detonation impacts on different mediums, including water and other metal mediums, is tested and verified here. Then the model is applied to the simulation of underwater contact explosion problem. In the simulation, deformation of structure under explosion loads, as well as second shock wave, are studied here. <ack> <x xml:space="preserve"> Acknowledgements </x> This work is supported by the Foundation for Innovative Research Groups of the National Natural Science Foundation of China (No. 509221001), the National Program on the Key Basic Research Project of China, 973 program (No. 2010CB832704), and Doctoral Research Foundation of Liaoning Province (No. 20091012). The financial contributions are gratefully acknowledged. </ack>